Coffee of São Paulo: Virtual aroma - Guimarães, Marcelo De P; Silva, Edna de Mello; Faria, Alessandro; Ferrao, André M De Argollo; Dias, Diego R C (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2022: Anais do XXIV Simpósio de Realidade Virtual e Aumentada, 2022)
This paper aims to present a multisensory (visual, auditory, and olfactory) virtual reality experience concerning the history and production process of a beverage that influences habits, pleasures, interactions with family and friends, and work: coffee. The visitor is immersed in a 3D (three-dimensional) traditional farm from 19th century to experience harvesting, roasting, and coffee preparation, and to learn historical facts. This simulation has an olfactory display that allows the aroma of coffee to be part of the user’s experience. This multisensory experience is innovative and surprising, and it brings visitors closer to the traditional coffee production process. This project was exhibited in the Major Novaes Museum (Cruzeiro, SP).